“Full house” lupus nephritis with negative serology: a case report - Guerrero, José L.; Lucas, Amparo N.; García, Gema Y.; Montesdeoca, María L.; Mendieta, Melissa M. (International Journal of Research in Medical Sciences, 2025)
Kidney disease is the leading cause of morbidity and mortality in systemic lupus erythematosus (SLE). Among the histological types of lupus nephritis, membranous lupus nephritis accounts for only one-fifth of all cases, with immunofluorescence being essential for diagnosis. The long-term prognosis of lupus nephritis is uncertain, with a significant percentage progressing to stage 5D chronic kidney disease (10 to 20%). Existing evidence on the relative efficacy of different therapies is limited. The authors present the clinical case of a 28-year-old male patient with a kidney biopsy revealing lupus nephritis, in the absence of other clinical and laboratory manifestations of SLE. Until a few years ago, 40% of patients with severe forms of lupus nephritis progressed to death or chronic kidney failure within five years of disease onset. Today, this pessimistic prognosis has improved significantly thanks to anatomical, clinical, and therapeutic approaches.